Bioinformatics An Introduction (Third Edition) - Ramsden, Jeremy (Springer, 2015)
The publication of this third edition has provided the opportunity to carefully scrutinize the entire contents and update them wherever necessary. Overview and aims, organization and features, and target audiences remain unchanged. The main additions are in Part III (Applications), which has acquired new sections or chapters on the seemingly ever-expanding “omics”—now metagenomics, toxicogenomics, glycomics, lipidomics, microbiomics, and phenomics are all covered, albeit mostly briefly. The increasing involvement of information theory with ecosystems man agement, which is undoubtedly a part of biology, was felt to warrant a new chapter on that topic. The nervous system has also been explicitly included: it is indubitably an information processor and at the same time biological and, therefore, certainly warrants inclusion, although consideration of the vastness of the topic and its extensive coverage elsewhere has kept the corresponding chapter brief. A section on the automation of biological research now concludes the work...